2021
DOI: 10.1093/noajnl/vdab082
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diffusion MRI as a biomarker for efficacy using randomized phase III trial of bevacizumab with or without VB-111 in recurrent glioblastoma

Abstract: Background Evidence from single and multicenter phase II trials have suggested diffusion MRI is a predictive imaging biomarker for survival benefit in recurrent glioblastoma (rGBM) treated with anti-VEGF therapy. The current study confirms these findings in a large, randomized phase III clinical trial. Methods Patients with rGBM were enrolled in a phase III randomized (1:1), controlled trial (NCT02511405) to compare the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ellingston et al [47] found an association between lower pretreatment ADC values and lower progression-free survival and overall survival in patients with recurrent glioblastoma treated with bevacizumab. Analyzing data from a randomized, controlled phase III trial comparing the efficacy of bevacizumab with and without VB-111, the same group [48] found that baseline tumor volume and data derived from ADC histogram analysis were predictive biomarkers of overall survival. As in our study, the histograms were generated from ADC values extracted from contrast-enhancing regions in T1-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Ellingston et al [47] found an association between lower pretreatment ADC values and lower progression-free survival and overall survival in patients with recurrent glioblastoma treated with bevacizumab. Analyzing data from a randomized, controlled phase III trial comparing the efficacy of bevacizumab with and without VB-111, the same group [48] found that baseline tumor volume and data derived from ADC histogram analysis were predictive biomarkers of overall survival. As in our study, the histograms were generated from ADC values extracted from contrast-enhancing regions in T1-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher baseline Ktrans and larger drop in extracellular volume fraction (EVF) was correlated with longer PFS (p < 0.05) ( Sahani et al, 2013 ). Interestingly, similar imaging biomarkers have also been investigated in patients with recurrent glioblastoma treated with cediranib, an inhibitor of VEGFRs ( Batchelor et al, 2007 ; Sorensen et al, 2009 , 2012 ) or bevacizumab and bevacizumab plus ofranergene obadenovec ( Ellingson et al, 2021 ). These studies demonstrated that increased tumor blood prefusion and vessel normalization were associated with longer PFS and OS.…”
Section: Predictive Immune/vascular Biomarkers For Atezolizumab Plus ...mentioning
confidence: 99%